Nematodes from terrestrial, freshwater and brackish water habitats in Belgium: an updated list with special emphasis on compost nematodes - Steel, Hanne; Coomans, August; Decraemer, Wilfrida; Moens, Tom; Bert, Wim (Zootaxa, 2014)
A study of nematodes from a semi-artificial and controlled composting process in Eastern Flanders revealed 35 taxa, 21 of which were new records for Belgium. An updated checklist of free-living, plant-parasitic and entomopathogenic nematodes from terrestrial, freshwater and brackish water habitats in Belgium is presented. The Belgian non-marine nematofauna comprises 418 taxa, representing 4 subclasses, 14 orders, and 76 families. In total 127 new records were added: i.e. 21 from the newly explored compost habitat, 7 from freshwater samples and 99 from published data in literature.